Time to revisit oil palm-livestock integration in the wake of United Nations Sustainable Development Goals SDGs - Azhar, Badrul; Tohiran, Kamil Azmi; Nobilly, Frisco; Zulkifli, Raja; Syakir, Muhammad Izzuddin; Ishak, Zulkifli; Razi, Norhisham; Oon, Aqilah; Shahdan, Ahmad; Maxwell, Thomas M. R. (Frontiers, 2021)
To date, the idea of using livestock animals as biological tools to manage weeds, sequester carbon, and boost food security in oil palm plantations has not been seriously considered by industry stakeholders of major producing countries (e.g., Indonesia, Malaysia, Thailand, Colombia, and Nigeria). We revisit the integration of oil palm cultivation with livestock farming as a silvopastoral agroforestry practice in the wake of Sustainable Development Goals (SDGs). Oil palm-livestock integration has the potential to promote sustainable palm oil production because it can provide multiple environmental and socio-economic benefits, including carbon sequestration, restoring top soil, improving ecosystem biodiversity, reducing pesticide and fertilizer inputs, and boosting national food security. In contrast to monocultural outputs of most conventional plantations, an oil palm silvopastoral system is an ideal way to address the global food insecurity challenge as it produces bioenergy, vegetable oil/fat and animal-based protein sources (e.g., red meat). In addition, the potential of contract targeted grazing could be considered as a new type of business and income diversification for rural people. Oil palm-livestock integration is a strategy by the palm oil industry to achieve multiple SDGs. Out of the 17 SDGs, oil palm-livestock integration is likely to deliver nine SDGs. Palm oil certification bodies should recognize oil palm-livestock integration as a biological control method in weed management practices. We recommend that oil palm-livestock integration should be promoted to revitalize sustainable palm oil production and strategic biodiversity conservation policy. Policy makers should encourage major players in the palm oil industry to practice oil palm-livestock integration.